Using simulated wildland fire to assess microbial survival at multiple depths from biocrust and bare soils - Palmer, Brianne; Pietrasiak, Nicole; Cobb, Polina; Lipson, David (Frontiers in Microbiology, 2023)
Introduction Surface soil microbial communities are directly exposed to the heat from wildland fires. Due to this, the microbial community composition may be stratified within the soil profile with more heat tolerant microbes near the surface and less heat tolerant microbes, or mobile species found deeper in the soil. Biological soil crusts, biocrusts, are found on the soil surface and contain a diverse microbial community that is directly exposed to the heat from wildland fires. Methods Here, we used a simulated fire mesocosm along with a culture-based approach and molecular characterization of microbial isolates to understand the stratification of biocrust and bare soil microbes after low severity (450°C) and high severity (600°C) fires. We cultured and sequenced microbial isolates from 2 to 6 cm depth from both fire types. Results The isolates were stratified along the soil depth. Green algal isolates were less thermotolerant and found in the deeper depths (4–6 cm) and the control soils, while several cyanobacteria in Oscillatoriales, Synechococcales, and Nostocales were found at 2–3 cm depth for both fire temperatures. An Alphaproteobacteria isolate was common across several depths, both fire types, and both fire temperatures. Furthermore, we used RNA sequencing at three depths after the high severity fire and one control to determine what microbial community is active following a fire. The community was dominated by Gammaproteobacteria, however some Cyanobacteria ASVs were also present. Discussion Here we show evidence of stratification of soil and biocrust microbes after a fire and provide evidence that these microbes are able to survive the heat from the fire by living just below the soil surface. This is a steppingstone for future work on the mechanisms of microbial survival after fire and the role of soil insulation in creating resilient communities.